São Tomé and Príncipe 1975-2015: politics and economy in a former plantation colony - Seibert, G. (Estudos Ibero-Americanos, 2016)
After independence in 1975 Sao Tome and Principe became a socialist one-party state. The regime nationalized the cocoa plantations and the entire economy. As the country lacked adequately trained people, within a few years the local economy was run down. Due to economic failure, in 1990 the regime introduced multiparty democracy and a free-market economy. Despite political instability provoked by consecutive changes of government, democracy has done relatively well. However, the economy has been ailing, since consecutive governments failed to recover the cocoa sector and diversify the economy. Prospects of becoming an oil producer that emerged in the 1990s have not materialized either, since commercially viable oil has not been discovered. Consequently, for many years the small country has become completely dependent on international aid. The article analyses the archipelago's policies and economy over the past forty years.